Ghana Digital Economy Diagnostic - World Bank Group (World Bank, Washington, DC, 2020)
Universal adoption and effective application of digital technologies are expected to characterize economies of the future, shaping their ability to succeed in the global marketplace and offer a better quality of life for their citizens. Disruptive technologies are already altering traditional business models and pathways to development, yielding significant gains, increased convenience, as well as supporting better access to services for consumers. In 2016, the digital economy was worth an estimated 11.5 trillion dollars worldwide, equivalent to 15.5 percent of global GDP. It is forecast to reach 25 percent in less than a decade, far outpacing the growth of the ‘traditional’ economy (Huawei and Oxford Economics 2016). Mobile money is driving financial inclusion, particularly in Sub-Saharan Africa, with the number of accounts doubling to 21 percent between 2014-17. African e-commerce is also rapidly growing, at an estimated annual rate of 40 percent. Over the past five years, there has been a tenfold increase across the region in the supply of new intermediaries such as incubators, accelerators, and technology hubs, amongst others, numbering more than 400 across Africa today. The digital economy in Africa is expected to grow to over 300 billion dollars by 2025 (McKinsey 2013). Ghana has made substantial progress on financial inclusion, due in large part to growth in DFS. According to the World Bank’s Global Findex, the share of Ghanaian adults (over 15 years of age) with a formal financial account increased by 42 percent between 2014 and 2015. As a result, nearly 6 in 10 adults had formal access in 2017. With mobile account ownership increasing by nearly 200 percent between 2014 and 2017, mobile money has become the preferred payment alternative to cash when measured in terms of transaction volumes. In May 2018, the Bank of Ghana mandated that all mobile money providers connect to GHLink, with full interoperability between mobile money providers and banks introduced in December 2018.